Data protection in the EU's internal security cooperation: Fundamental rights vs. effective cooperation? - Roderick Parkes; Marie McGinley (Stiftung Wissenschaft und Politik (SWP), 2007)
European home affairs cooperation has often been characterised by the disinclination of national security officials to submit themselves to robust common rules, institutions and human rights standards. Cooperation has frequently occurred outside the formal framework of the European Union (EU) at a more informal and ad-hoc level. Even within the EU framework, rights standards as well as judicial and parliamentary oversight remain patchy.This reluctance to submit to robust rules and oversight is commonly viewed as a legitimate means of overcoming the perceived tension at the heart of efforts to provide security in liberal democratic systems: The aim of achieving effectiveness in internal security activities is perceived to be undermined by the exigencies of parliamentary and judicial oversight, as well as - more specifically - human rights protection.The present paper questions this assumed tension, showing that, besides safeguarding the freedoms of individuals, common rules and rights standards backed by sturdy oversight structures can actually have beneficial implications for the effectiveness of internal security cooperation. It suggests that the disinclination of security officials to submit to such frameworks for cooperation may have more to do with their desire to retain their autonomy vis-à-vis other actors, and less to do with a desire to engage in effective cooperation. Examining the latest efforts to further EU data exchange, as well as the rights standards binding this exchange, the paper highlights the importance of introducing robust data protection rules, particularly in those areas where they would be conducive not only to ensuring the privacy of individuals but also to effective cooperation. (SWP Research Papers)
Keywords: 320